A Case of Infantile Fungal Urinary Tract Infection - Wonhee Cho; Young Min Jo; Yun Kyo Oh; Ji Woo Rim; Won Uk Lee; Kyongeun Choi; Jeong Hee Ko; Yeon Jin Jeon; Yumi Choi (Korean Society of Pediatric Nephrology, 2019)
Urinary tract infection is common in the pediatric population. The most common causative agents are bacteria, among which Escherichia coli is the most frequent uropathogen. Although fungal urinary tract infection is rare in the healthy pediatric population, it is relatively common among hospitalized patients. Fungus may be isolated from the urine of immunocompromised patients or that of patients with indwelling catheters. The most common cause of funguria is Candida albicans. Although more than 50% of Candida isolates belong to non-albicans Candida , the prevalence of non-albicans candiduria is increasing. Herein, we report a case of community-acquired candiduria in a 4-month-old immunocompetent male infant who had bilateral vesicoureteral reflux and was administered antibiotic prophylaxis. He was diagnosed with urinary tract infection caused by Candida lusitaniae and was managed with fluconazole.